A Survey of Indoor Localization Techniques for Smartphones - Risteska Stojkoska, Biljana; Nizetic Kosovic, Ivana; Jagušt, Tomislav (My University, 2016)
Pervasive and ubiquity computing are expected to expand the development of new business oriented mobile applications. Knowing the exact physical location of the wireless devices is crucial for providing awareness of these applications. Many algorithms have been proposed for wireless localization, but most of them are designed for outdoor localization by using Global Positioning System (GPS) signals. In indoor environments, the GPS is not available, which makes localizations not trivial. This paper surveys state-of-the-art attempts toward efficient indoor localization for smartphones. We define a taxonomy used for better classification of the algorithms. Furthermore, we describe the characteristics of modern indoor positioning systems, as well as the challenges associated with the localization techniques. Finally, we provide real experiments using different smartphone models in order to discover typical problems that occur when signal strength is used as a range measurement technique in indoor localization systems.
Keywords: indoor localization · taxonomy · smartphone · RSSI